Speaking the language of the patient: indigenous language policy and practice - Margaret Matthews; Jacqueline van Wyk (South African Family Practice)
South Africa faces numerous challenges in healthcare, with the result that communities in many rural provinces are grossly underserved. These problems are compounded when doctors are unable to communicate with their patients. IsiZulu is spoken by most people in KwaZulu-Natal. Older and rural patients often present as monolingual isiZulu speakers. The need and ability to speak an indigenous language is emphasised in communication, identified as a core competency for doctors. The benefits of language-concordant health care have been documented, and policies at national, regional and institutional level provide for language diversity. As first-language English users, medical students have to be trained to become competent in speaking isiZulu. This mixed-method study assessed the knowledge, attitudes and perceptions of third-year students who had received isiZulu-training during their first year at the University of KwaZulu-Natal. The results indicated an improvement in students’ communicative competence. In general, positive attitudes were held by the students towards the language, but there was a perceived need for additional input in order for the students to become competent.